THE IMPLEMENTATION OF BLUE OCEAN STRATEGY TO CREATE A MARKET NICHE - Hanifah Hanifah; Aswanti Setyawati; Reni Dian Octaviani (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
Business competition among companies has led to major changes. Thus, companies must be responsive to the business strategy implemented [by competitors] and create business opportunities that can generate profits. One way is to implement Blue Ocean Strategy that allows businesses to create a niche market to get out of the red ocean competition so that competition becomes irrelevant. This study is aimed at analyzing the condition of a company implementing the Blue Ocean strategy represented by PT Kintetsu World Express in the period of 2012-2013. By using the descriptive method and the theories in strategic management, it is clearly visible how the implementation of Blue Ocean Strategy by PT Kintetsu World Express Indonesia can make the company win the competition and becomes the “Market Leader”. Making the Internal Process Company (IPF - BOS) in order to optimize the implementation of Blue Ocean Strategy, making the value of the company and the products to be better in the consumer’s perspective.